A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India - Giri, Varad B.; Deepak, V.; Captain, Ashok; Das, Abhijit; Das, Sandeep; Rajkumar, K. P.; Rathish, R. L.; Gower, David J. (Zootaxa, 2017)
Based on analyses of new DNA sequence data for two nuclear (rag1, cmos) and three mitochondrial (16s, cytb, nd4) genes, the Indian snake genus Rhabdops is a natricine. Variation in geography, DNA sequences, the number of ventral scales, pattern and colour for samples of Rhabdops from along the Western Ghats region of peninsular India is concordant, discontinuous and bimodal. We recognise populations from the northern Western Ghats as distinct specifically from the more southerly R. olivaceus and describe Rhabdops aquaticus sp. nov. based on a series of eight specimens from two localities in the Northern Western Ghats. Rhabdops aquaticus sp. nov. is associated particularly with upland laterite plateaus and their associated streams, a threatened habitat within its known distribution.